2019
DOI: 10.1097/cmr.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Routine retrieval of pelvic sentinel lymph nodes for melanoma rarely adds prognostic information or alters management

Abstract: Pelvic sentinel lymph nodes (SLNs) are commonly identified during inguinal SLN biopsy for melanoma, but retrieval is not uniform among surgeons/centers. Few studies have assessed rates of micrometastases in pelvic versus superficial inguinal SLNs. Previous studies suggested that presence of pelvic SLNs was predicted by aggressive pathologic features and that their presence portended a worse prognosis. The objectives of this study were to examine presurgical predictors of pelvic SLNs among patients undergoing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…We did not find poorer disease-free survival or higher local (groin) nodal recurrence rates in patients with drainage to PSLNs. Swords et al 10 and Vuoristo et al 11 reported similar findings. Karakousis et al 8 did not detect a difference in the pelvic recurrence rates, but found that drainage to PSLNs is associated with marginally lower disease-free survival if SSLNs were histologically negative.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We did not find poorer disease-free survival or higher local (groin) nodal recurrence rates in patients with drainage to PSLNs. Swords et al 10 and Vuoristo et al 11 reported similar findings. Karakousis et al 8 did not detect a difference in the pelvic recurrence rates, but found that drainage to PSLNs is associated with marginally lower disease-free survival if SSLNs were histologically negative.…”
Section: Discussionmentioning
confidence: 61%
“…Other predictive factors have been found to be older age, greater Breslow thickness, and melanoma subtype. 811 Regarding the melanoma positivity of PSLNs, it is associated with male sex, tumor thickness, melanoma subtype, location in feet, and higher radioactivity count of the node. 9,11 However, 30.8% of patients with PSLN had positive SSLN in SLNB, when patients without PSLN, the rate was 17.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no survival benefit and the impact on staging is minimal, what remains to justify routine retrieval of PSLNs? Creating precise criteria for harvesting pelvic lymph nodes warrants randomized controlled trials or at least a large multicentre retrospective study, as suggested by Swords and colleagues 8 . Although only few studies exist on the importance of PSLNs, they mostly agree on the very limited impact of PSLNs on staging and treatment of PSLNs 6–8 .…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Several studies have attempted to identify factors that predict pelvic lymph node involvement, but no definitive relationships have been established. 4,5 The lack of predictive factors coupled with worse prognosis with pelvic node involvement forms the basis of the support for performing pelvic lymphadenectomy, albeit in select patients.…”
mentioning
confidence: 99%